Investment In Egypt : (Fund for Multinational Management Education, 1975)
This book aims to give interested readers an insight into the upcoming Egyptian investment climate by providing a thorough analysis of the top twelve areas of investment in the country. Upon reading it, readers will have an idea of where the core areas of investment lie, the advantages of investing in Egypt, and the legal processes which must be incurred to successfully carry out a project within the various sectors.